PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, KOMUNIKASI INTERPERSONAL, DAN KOMITMEN ORGANISASIONAL TERHADAP KUALITAS PELAYANAN PUBLIK PADA KANTOR PELAYANAN KEKAYAAN NEGARA DAN LELANG DENPASAR - Ni Wayan Ari Sudiartini; Ni Kadek Ari Sintya Dewi; Sri Ernawati Zunaidin (LPSDI Bina Patria, 2023)
Quality services are services that are supported by the actions of good, responsible, fair, fast and precise officers where this greatly affects the quality of service of an agency. improving the quality of public services is certainly not easy, because it cannot be separated from various influencing factors such as the influence of transformational leadership, interpersonal communication and organizational commitment, this study aims to determine the effect of transformational leadership, interpersonal communication and organizational commitment on the quality of public services in Denpasar State Property and Auction Service Office. This research was conducted at the Denpasar State Property and Auction Service Office, in this study a sample of 42 people who were employees of the Denpasar State Property and Auction Service Office. In this study using quantitative research methods sourced from primary data, data collection was carried out using observation, interviews, documentation studies, literature and questionnaires. The data analysis technique used research instrument test, classical assumption test, descriptive analysis, multiple regression analysis, and model feasibility test. The results show that (1) transformational leadership partially has a significant effect on the quality of public services at the Denpasar State Property and Auction Service Office, this is evidenced by the tcount value is greater than the ttable value (3.435 > 1.686), and the significance value is smaller than 0.05 (0.001 < 0.05). (2) Interpersonal communication partially has a significant effect on the quality of public services at the Denpasar State Property and Auction Service Office, this is evidenced by the tcount value greater than the ttable value (3.978 > 1.686) and the significance value less than 0.05 (0.001) <0.05). (3) Organizational commitment partially has a significant effect on the quality of public services at the Denpasar State Property and Auction Service Office, this is evidenced by the tcount value greater than the ttable value (2.318 > 1.686) and the significance value less than 0.05 (0.001) <0.05). (4) Transformational Leadership, Interpersonal Communication, Organizational Commitment simultaneously have a significant effect on the quality of public services at the Denpasar State Property and Auction Service Office, this is evidenced by the fcount value greater than ftable (13.198 > 2.852), and a significance value of 0.001 less than 0.05 (0.001 < 0.05).